Kecerdasan Emosional dan Kecerdasan Spiritual Pengaruhnya terhadap Kepuasan Kerja dan Kinerja Karyawan (Studi di Lembaga Penjaminan Mutu Pendidikan (LPMP) Nusa Tenggara Barat) - Hidayati, Ida Nur; Setiawan, Margono; Solimun (Jurnal Aplikasi Manajemen, 2013)
This study analyzes the influence of emotional intelligence and spiritual intelligence to job satisfaction and performance of employees in the Education Quality Assurance Agency (LPMP) West Nusa Tenggara. The study population was all employees LPMP West Nusa Tenggara with the status of civil servants and the rest of the population sampled (saturated samples). Analysis tool used is GSCA (Generalized structured component analysis). The results show that emotional intelligence does not significantlyinfluence job satisfaction and performance, while the spiritual intelligence had a significant influence on job satisfaction and performance. Furthermore, job satisfaction has a significant influence on employee job satisfaction.